Preferensi Belanja Konsumen Pasar Tradisional dan Pasar Modern di Kota Banjarmasin (Studi Kasus Pasar Kuripan dan Minimarket) - Fitriyani, Amalia (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
The research aims to identify the characteristics of respondents and consumer households and their shopping preferences at Kuripan Market and minimarkets (Indomaret and Alfamart). The research uses quantitative descriptive analysis. The number of households within a 500 meter radius of the Kuripan Market location reached 348 households. The minimum sample is 78 households. Data collection techniques through closed interviews in questionnaires. The research results show that around 70% of respondents prefer to shop at Kuripan Market, while 30% choose minimarkets. The main reason for choosing Kuripan Market is the availability of fresh fish, vegetables and fruit, as well as bargaining. On the other hand, 39% of respondents chose to shop at Indomaret, while 48% chose Alfamart. The main reasons for shopping at minimarkets are closer distance, more affordable prices, a more complete selection of goods, as well as cleanliness and comfort.